Vulnerability in the arena of strength: An analysis of Christian sermons in the context of international sporting events. - Graff-Kallevåg, Kristin; Stålsett, Sturla J. (Studia Theologica, 2022)
There is an ambiguity inherent in vulnerability as a part of human life. Beyond mere limitation, recent interdisciplinary research shows that the condition of vulnerability also contains essential life-sustaining resources. This ambiguity is particularly interesting in the context of embodied competition, such as sports. The present study of Christian sermons held on the occasion of international sporting events explores to what degree and in what way the homilies mobilize religious resources to shed light on this ambivalence of vulnerability. The study shows that the sermons in general tend to confirm rather than challenge a conventional conceptualization of vulnerability as limitation. However, it also shows a critical potential, explicitly present in some of the sermons, of mobilizing theological and religious resources for providing a more multi-faceted and even affirmative interpretation of vulnerability in the context of competitive sports.